The development and optimization of face-perpendicular preconditioning technique for development ends - Sengani, F.; Zvarivadza, T. (CRC Press, 2022)
Face perpendicular preconditioning practice is one of the mechanisms used in deep level gold mines to transfer stress far ahead from the face on the development ends called destress cuts. Although face perpendicular preconditioning practice has been implemented in gold mines, rockbursts are still considered as the most problematic issue faced by deep level gold mines. This has led to minor injuries, serious injuries, machinery damage and delays the daily production of a mine. This investigation aims at highlighting the effectiveness of face-perpendicular preconditioning practices that were developed for development ends in mechanized gold mines. The investigation involve the comparison between four face and five face-perpendicular preconditioning holes practice at a deep level gold mine. The results of the study indicated that five face-perpendicular preconditioning practice is much more effective than four face-perpendicular preconditioning holes. The results were certified by adequate fracturing on the mining face, improvement of fracturing on the vicinity of the sockets (preconditioning sockets) and rapid decrease on the hangingwall fracturing. Ground Penetrating Radar (GPR) confirmed the improvement on face fracturing and sockets fracturing, lastly micro seismicity also shows less seismic events occurring during the implementation of five face-perpendicular preconditioning than four face-perpendicular preconditioning practice.